Pharmacist’s time spent: Space for Pharmacy-based Interventions and Consultation TimE (SPICE)—an observational time and motion study - Ruth Webster; Tracey-Lea Laba; Rohina Joshi; Suzanne Robinson; Richard Norman; Christine Balane; Ajay Karia; Elin Lehnbom; Iva Durakovic (BMJ Open, 2022)
Objective To describe the pharmacists’ workflow, including tasks and time spent, to better understand their work capacity.Design Cross-sectional, observational, time and motion study.Setting Community pharmacies in Western Australia and New South Wales, Australia.Participants Currently registered and practising pharmacists were approached using snowball sampling and selected using purposive techniques to obtain balance representation of metropolitan and rural pharmacies, as well as high and low script volumes where possible.Results Twenty-four pharmacists across 15 pharmacies participated during the 135 sessions totalling over 274 hours of observation. Dispensing (30%), indirect patient services (17%), counselling (15%) and professional management activities (15%) were the top four duties pharmacists performed, while only 2% of time was spent on professional services such as pain clinics and influenza vaccinations. Tasks were frequently interrupted and often performed simultaneously. Breaks and consumer-contact times were limited. More time was spent on professional service activities in non-metropolitan pharmacies, in pharmacies with greater daily prescription volumes and those with one or more support pharmacists.Conclusions This is the first study to quantify the pharmacists’ tasks in Australian community pharmacies. Much time is being spent on dispensing, supply and management activities with little time for providing additional professional services. An extra supporting pharmacist is likely necessary to increase professional services. These findings could support future research around barriers and enablers of conducive workflows and of extended professional services.